Key Technology of Smart Network in Mobile Internet Environment - Yuan Zhang; Huiling Zhao (Dianxin kexue)
The key technology about smart network in mobile internet environment was described. Awareness, PCC, openness were the key characters of smart networks. Awareness capability is the understructure, PCC is the core technology, and open the network capabilities to terminal and service will provide better user experience and more services.